A 30‐GHz low‐power CMOS LNA for 5G communication systems. Issue 3 (22nd September 2020) - Liu, Jiye; Wu, Liang; Zhu, Zhangming; Liu, Shubin
Abstract: This paper presents theoretical analysis and design procedures for low noise amplifiers (LNAs) in advanced CMOS technologies. For demonstration, a 30‐GHz LNA designed for 5G millimeter‐wave communication systems was fabricated in a 65‐nm CMOS process. It provides a power gain of 22.6 dB with a noise figure of 3.2 dB while drawing 7.3 mW from a 1.2 V supply.